(3fXQjI h JWHjbs - (3UGOb Ydj(B, (3GdLHhQjs; (3YOfGf OGhO GdYPGQj(B, s ((3YeGf(B:s (3OGQ LQjQ(B,s, 2010)
(3GdeLehYGJ , GdOhGd h GdGSS ,GTJbGb GdOhGd , GdeUahaGJ , GdJcGed , GdHQeLI GdNWjI , fXQjI fSjL GdYfcHhJ , fXQjI GdeSJNOe `` GdefJL(B.s
(3eQGLY U(B.187s
Keywords: (3GdEbJUGO GdQjGVjs; (3GdGbJUGOs; (3GdQjGVjGJs